LEGALITAS KELAYAKAN DAN KOMPETENSI DOKTER DALAM MEMBERIKAN LAYANAN TINDAKAN MEDIK DI KLINIK KECANTIKAN - Rusyad, Zahir; Hakim, Purnawirawan Dwikora; Hakim, Lukman; Wulandari, Novita (Journal of Innovation Research and Knowledge, 2025)
The growing practice of aesthetic medicine in Indonesia raises the demand for legal certainty regarding the legitimacy of medical procedures performed by doctors in beauty clinics. This study aims to examine the legal framework governing such practices by analyzing the scope of medical authority under health law, the application of the lex specialis principle, the role of informed consent, and the ethical and legal responsibilities of the medical profession. The research further explores the legal and operational requirements of beauty clinics as licensed healthcare facilities, including professional certification, equipment and facility standards, and risk management systems. Within the legal context of aesthetic medical procedures conducted in beauty clinics, this study emphasizes the importance of regulatory compliance, adequate medical competence, and professional oversight. The findings indicate that aesthetic medical procedures can only be deemed lawful if they fulfill legal, ethical, and professional standards as outlined by statutory regulations and medical ethical codes. Therefore, stronger regulatory frameworks and supervision mechanisms are crucial to ensuring patient protection and maintaining the integrity of the medical profession.